THE PROCESS OF ENHANCED OIL RECOVERY (EOR)USING ALKALINE SURFACTANT (AS) FLOODING ON SUKOWATI CRUDE OIL: A COMPARISON STUDY OF MIXED SURFACTANT - Buanasari, Buanasari; Pramudono, Bambang (Universitas Negeri Semarang, 2017)
We investigated six mixed surfactants for effectiveness in enhanced oil recovery (EOR). The selected surfactant formulation were tested for EOR using coreflood tests beneath sandstones. There are four objectives in this research. The first objective would examine synergism of surfactant mixtures, i.e., MES-SLS; MES- LAS; MES-DEA; MES-Tween 80; MES-BAC; and BAC-Tween 80. The next study examines the optimal ratio of the best surfactant mixture. The next step is to determine the best alkali between NaOH and Na2CO3. The final objective would determine the optimal concentration of alkaline in this formulation. Surfactant formulation would use brine 5000 ppm. This formulation injected with a flow rate of 10 ml/s at temperature of 70oC for 3 minutes beneath sandstones. Oil recovery results and the IFT value are observed response in this study. This research has found MES-DEA (Â½: 1) and alkali sodium carbonate 1% wt/v as the best formulations. This formulation has given 32,88% wt oil recovery and IFT value of 3,29 x 10-1 mN/m.